Excitation of correlated chain of nonlinear ion-acoustic solitary perturbations of finite amplitude, accelerating ions in current-carrying magnetosphere plasma - Azarenkov, N.A.; Yegorov, A.M.; Frolova, D.Yu.; Lapshin, V.I.; Maslov, V.I.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2004)
In this paper the chain of correlated solitary perturbations of finite amplitude, accelerating ions in the magnetosphere, is investigated.